Effect of political stability on environmental quality: long-run and asymmetric evidence from Iceland by non-linear approaches - Kilic Depren, Serpil; Kartal, Mustafa Tevfik; Kirikkaleli, Dervis; Depren, Ozer (SPRINGER, 2023)
The study researches the long-run and asymmetric effect of political stability (PS) on environmental quality. In this respect, this study focuses on Iceland because it is a politically stable country; investigates the effect of the political risk index (PRI) considering also trade openness (TRA), primary energy consumption (EC), and economic growth (GDP) on carbon dioxide (CO2) emissions; includes data from 1995/Q1 to 2019/Q4; and performs a non-linear autoregressive distributed lag model (NARDL) as the main model. Also, a fully modified ordinary least squares (FMOLS) is performed for robustness. The outcomes show that (i) positive and negative changes in the PS have a significant effect on CO2 emissions, whereas negative shocks are much stronger; (ii) positive shocks in the TRA have a decreasing effect; (iii) positive shocks in the EC have an increasing effect, whereas negative shocks have a decreasing effect on CO2 emissions; (iv) positive and negative shocks in the GDP have significantly increasing effect; (v) negative shocks in the EC and GDP are much powerful than positive shocks; (vi) the results of FMOLS validate the robustness of the NARDL outcomes. Thus, the findings confirm the contributing role of the PS in sustaining environmental quality in Iceland, which should be considered by policymakers, to achieve the carbon-neutrality aim of the country.
Keywords: Political stability; Environmental quality; Nonlinear approaches; Iceland; Environmental Sciences & Ecology